Renzhen xuexi Mao zhuxi zhuzuo shenru pipan "Sirenbang" fangemingde xiuzheng zhuyi daolu - Sun Bin,
'We must earnestly study the writings of Chairman Mao to deepen the criticism of the counter-revolutionary revisionist line of the "Gang of Four"'. Printno. 8118.336. Anti-Gang of Four.